2022
DOI: 10.3389/fmed.2022.1031915
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of probiotics supplementation on occurrence of gestational diabetes mellitus: A systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundGestational diabetes mellitus (GDM) is a health challenge during pregnancy and is associated with adverse effects. Dysbiosis of the gut microbiota may play a role in developing inflammation and insulin resistance observed in GDM. Probiotics are supposed to be influential in preventing GDM since they can alter the composition of microbiota in the intestine. Despite the existing studies on the therapeutic effects of probiotics in women with GDM, in this study we aim to systematically review and meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…No effect of probiotics on the development of GDM in higher-risk women was found, consistent with the results of a Cochrane review [ 11 ]. However, in contrast, a recent meta-analysis (n = 10) showed a significant reduction of GDM with probiotic supplementation in the general antenatal population [ 117 ]. Furthermore, metformin was not found to be effective in preventing GDM in higher risk pregnant women.…”
Section: Discussionmentioning
confidence: 96%
“…No effect of probiotics on the development of GDM in higher-risk women was found, consistent with the results of a Cochrane review [ 11 ]. However, in contrast, a recent meta-analysis (n = 10) showed a significant reduction of GDM with probiotic supplementation in the general antenatal population [ 117 ]. Furthermore, metformin was not found to be effective in preventing GDM in higher risk pregnant women.…”
Section: Discussionmentioning
confidence: 96%
“…Probiotics have a positive effect on preventing pregnancy complications. In GDM, a meta-analysis of 10 randomized control trials with 2921 pregnant women was published to assess the role of probiotics in GDM women ( 234 ). The results showed that probiotics reduced GDM incidence by 33%, and using multiple-strain probiotics had a greater effect on GDM.…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…The selection of an appropriate probiotic strain is important, which may impact the therapeutic effects of probiotics ( 234 ). Therefore, deeper investigation, including different strains of probiotics, was required in the future.…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Pakmehr et al (2022) focused on the preventive effects of probiotics on GD occurrence. The study concluded that while probiotics might reduce the incidence of GD, the evidence is not conclusive, and no significant benefits or harms related to probiotic supplements on secondary outcomes were observed [44]. Shahriari et al (2021) investigated the effects of probiotic supplementation from the early second trimester until the 24th week of pregnancy.…”
Section: Use Of Probiotics In Gestational Diabetesmentioning
confidence: 99%